Editorial - Nuñez Alberca, Alejandro (2024)
Nowadays, it surprises no one that the field of Communication Studies is inherently multidisciplinary. The past fifty years testify to the numerous trends and changes that have compelled communication researchers to seek new theoretical frameworks and paradigms due to transformations within the scientific field itself and the urgencies of civil society. Not long ago, Oliver et al. (2024), writing for Human Communication Research, described our era as marked by «accelerated technological changes, transformations in political discourse, evolutions in interpersonal communication, and a greater appreciation for the importance of diversity and inclusion» (p. 143). Amidst this circumstances, academic journals have themission to offer empirical studies that reflect the latest developments in the field (whether it be big data, artificial intelligence, disinformation, platform capitalisms, etc.), without neglecting the development of theories aimed at explaining their findings. This issue of Correspondencias & Análisis comprises works that seek to account for this diversity, but also for the important theorizing activity that the study of communication demands.